What is the learning model of physical education in the digital era? Literature review of various studies - Pungki Indarto; Nasuka Nasuka; M. Furqon Hidayatullah; Sulaiman Sulaiman; Heny Setyawati; Hermawan Pamot Raharjo; Didi Suryadi (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2024)
The digital age has changed the landscape of physical education (PE), with technology playing an important role in the learning process. This article reviews various studies on the use of technology in physical education to understand the trends, benefits, and challenges in implementing digital learning models. The search in this study used the Harzing Publish or Perish application. The search was initiated using the Scopus database with keywords ("learning model" AND "physical education" OR "sports education" AND "digital era"). Initially, 12.654 publications were identified through the database search (Scopus: 2,831 articles). After following exclusion criteria, only 10 articles remained. The search was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The review showed that technologies such as mobile apps, e-learning, virtual reality, digital media, and video games can improve student motivation, engagement, and understanding. However, challenges such as infrastructure limitations, user readiness, and potential reduction of physical aspects in physical learning need to be considered. Therefore, a balanced approach between the use of technology and physical activity is needed, as well as adequate support to maximize the benefits of technology in physical education. Further research is recommended to explore more effective strategies in integrating technology into physical education learning across different contexts. Although there are many studies on adolescent girls' lack of engagement in Physical Education (PE) in the literature, most only investigate the root causes, while few take initiatives to address the inherent problems.